Бенфотіамін та альфа-ліпоєва кислота у лікуванні автономної нейропатії серця у хворих на цукровий діабет 2-го типу - Сергієнко, В. О.; Сегін, В. Б.; Самір, Ажмі; Сергієнко, О. О. (Clinical Endocrinology and Endocrine Surgery, 2013)
The aim of this study was to assess the efficiency of benfotiamine and α-lipoic acid (α-LA) in the treatment of cardiovascular autonomic neuropathy (CAN) in patients with type 2 diabetes mellitus (type 2 DM). We have examined 70 patients with type 2 DM with established CAN. Treatment groups were sex and age-matched, there was no difference in duration of illness, HbA1c levels. Patients with type 2 DM and CAN were divided into four treatment groups: group A received traditional hypoglycemic therapy (n=15, control group), group B (n=12), in addition to traditional therapy received benfotiamine 300 mg/day; patients from group C (n=18) – α-LA 600 mg/day; group D (n=15) – 300 mg/day of benfotiamine in combination with 600 mg/day α-LA. Duration of the study was 3 months. As a result, no significant difference in HbA1c concentrations in the blood of patients with type 2 DM and CAN before and after treatment was found. It was established, that assignment of benfotiamine to patients with type 2 DM and CAN was not associated with significant changes in LDL, HDL, TG, total cholesterol and leptin levels, but contributes significant decrease of IRI, hsCRP and TNF- α concentrations. Usage of α-LA in the complex treatment of patients with type 2 DM and CAN contribute to significant decrease of LDL, total cholesterol, IRI, leptin and TNF-α concentrations. Combined usage of benfotiamine and α-LA in patients with type 2 DM and CAN is accompanied by more significant decrease of LDL, total cholesterol, IRI, hsCRP and TNF-α and increase of HDL concentration. Obtained results suggest that the efficacy of combined treatment with benfotiamine and α-LA has no connection with the improvement of diabetes compensation, but are as result of the direct pharmacological agents effect on the investigated metabolic parameters level.